Increased Bile Acid Synthesis and Deconjugation After Biliopancreatic Diversion - Ferrannini, Ele (Diabetes, 2015)
Biliopancreatic diversion (BPD) improves insulin sensitivity and decreases serum cholesterol out of proportion with weight loss. Mechanisms of these effects are unknown. One set of proposed contributors to metabolic improvements after bariatric surgeries is bile acids (BAs). We investigated the early and late effects of BPD on plasma BA levels, composition, and markers of BA synthesis in 15 patients with type 2 diabetes (T2D). We compared these to the early and late effects of Roux-en-Y gastric bypass (RYGB) in 22 patients with T2D and 16 with normal glucose tolerance. Seven weeks after BPD, insulin sensitivity had doubled and serum cholesterol had halved. At this time, BA synthesis markers and total plasma BAs, particularly unconjugated BAs, had markedly risen; this effect could not be entirely explained by low FGF19. In contrast, after RYGB, insulin sensitivity improved gradually with weight loss and cholesterol levels declined marginally; BA synthesis markers were decreased at an early time point (2 weeks) after surgery and returned to the normal range 1 year later. These findings indicate that BA synthesis contributes to the decreased serum cholesterol after BPD. Moreover, they suggest a potential role for altered enterohepatic circulation of BAs in improving insulin sensitivity and cholesterol metabolism after BPD.